1998
DOI: 10.1001/jama.279.5.371
|View full text |Cite
|
Sign up to set email alerts
|

Health Values of Hospitalized Patients 80 Years or Older

Abstract: Context.-Health values (utilities or preferences for health states) are often incorporated into clinical decisions and health care policy when issues of quality vs length of life arise, but little is known about health values of the very old. Objective.-To assess health values of older hospitalized patients, compare their values with those of their surrogate decision makers, investigate possible determinants of health values, and determine whether health values change over time. Design.-A prospective, longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(119 citation statements)
references
References 37 publications
4
114
0
1
Order By: Relevance
“…Elderly patients with multiple diseases represent all of these issues (12)(13)(14)(15). Further, a clear tendency towards inpatient care concentrating on acute incidents has been described (16), as well as the need for an integrated care management model for the care of elderly and chronically ill patients, which was recently pointed out in this journal (17).…”
Section: Main Text Backgroundmentioning
confidence: 99%
“…Elderly patients with multiple diseases represent all of these issues (12)(13)(14)(15). Further, a clear tendency towards inpatient care concentrating on acute incidents has been described (16), as well as the need for an integrated care management model for the care of elderly and chronically ill patients, which was recently pointed out in this journal (17).…”
Section: Main Text Backgroundmentioning
confidence: 99%
“…Researchers have also reported that patient values are higher than their surrogates believe (122,123). [Wide individual-to-individual variations in health values are common (36,82,123)].…”
Section: Relationship Between Patient and Community Preferencesmentioning
confidence: 99%
“…21,22 These results are similar to the findings of previous studies demonstrating the willingness of older persons to undergo intensive care unit treatment 23 and their unwillingness to trade off any amount of time in their current health for perfect health. 24 However, in the case of equivalent outcomes, the preference expressed by many of the respondents for treatment at home supports its explicit consideration and expansion as a treatment alternative for less severely ill patients. The lack of a strong association between preference and sociodemographic and health status implies that the only way to ascertain these preferences is to ask the patient directly.…”
Section: Commentmentioning
confidence: 99%